PENGEMBANGAN PROFESI DAN KARIR GURU DI SMP NEGERI 1 MUARA PINANG - zuzandi zuzandi; Connie Connie (Manajer Pendididikan, 2019)
Abstract: the general purpose of this research is describe development teacher profession and career in Public Junior High School Number One Muara Pinang. This research can be used for improvement career development of teachers to achieve in an education instution. The specially this research is: (1) how the system of assignment of professional development and career of teacher in Public Junior High School Number One Muara Pinang, (2) how the process of professional developmen and career in Public Junior High School Number One Muara Pinang, (3) how the results is be achieved from the professional development teacher and career in Public Junior High School Number One Muara Pinang. This research used descriptive qualitative method. The subject this research is headmaster,  the deputy of curiculum field and all of teachers in Public Junior High School Number One Muara Pinang. The conclusion of this research is, (1) the professional development system in Public Junior High School Number One Muara Pinang are expertise, skill, professionalism, and responsibility, to improve the teacher competense, the teacher follow the professional development process such as MGMP, KKG, PLPG, etc. From this training can improve their  competence, personal ability, pedagogik, professionalism, personal antitude and social, (2) the system professional development  and career  of the, they are giving an assignment , to increase of position and promotion of position. The result from professional development is professional developmen requires training  and mastery as well as specialized knowlodge.  Keyword: Professional Development, Career Development